Contemporary View of the Structural and Functional Peculiarities of the Skin, Items of Care and Prevention of Dermatological Pathology in Infants - Nikolay N. Murashkin; Eduard Т. Ambarchian; Roman V. Epishev; Alexander I. Materikin; Dmitriy V. Fedorov ("Paediatrician" Publishers LLC, 2018)
The article presents the modern knowledge of the structural and functional peculiarities of the skin in children. Information on the etiopathogenesis of a debut atopic dermatitis has been also given. The results of our own observations with an analysis of the clinical efficacy and safety of cosmetics based on highly purified lanolin and cotton extract in infants have been presented.